2007
DOI: 10.1210/en.2006-0933
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 Signaling Is Stimulated by Zinc Ions But Not by Obestatin

Abstract: GPR39 is an orphan member of the ghrelin receptor family that recently was suggested to be the receptor for obestatin, a peptide derived from the ghrelin precursor. Here, we compare the effect of obestatin to the effect of Zn(2+) on signal transduction and study the effect of obestatin on food intake. Although Zn(2+) stimulated inositol phosphate turnover, cAMP production, arrestin mobilization, as well as cAMP response element-dependent and serum response element-dependent transcriptional activity in GPR39-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
298
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(316 citation statements)
references
References 31 publications
9
298
2
7
Order By: Relevance
“…However, later studies were unable to repeat the results (Holst et al, 2007;Lauwers et al, 2006). Instead, Zn 2+ was suggested as a ligand for GPR39 (Holst et al, 2007). Activation of GPR39 increases cAMP accumulation and IP 3 turnover, suggesting that both the G s and G q pathways are involved.…”
Section: Gpr39mentioning
confidence: 97%
See 1 more Smart Citation
“…However, later studies were unable to repeat the results (Holst et al, 2007;Lauwers et al, 2006). Instead, Zn 2+ was suggested as a ligand for GPR39 (Holst et al, 2007). Activation of GPR39 increases cAMP accumulation and IP 3 turnover, suggesting that both the G s and G q pathways are involved.…”
Section: Gpr39mentioning
confidence: 97%
“…Obestatin, which is a peptide derived from the ghrelin precursor, was recently suggested as a ligand for GPR39 (Zhang et al, 2005). However, later studies were unable to repeat the results (Holst et al, 2007;Lauwers et al, 2006). Instead, Zn 2+ was suggested as a ligand for GPR39 (Holst et al, 2007).…”
Section: Gpr39mentioning
confidence: 99%
“…6 Since the original study, however, two other groups have failed to activate the GPR39 receptor with obestatin. 7,8 Initial studies showed that obestatin has opposing effects to ghrelin. When given centrally and peripherally to mice, it resulted in decreased food intake and suppressed gastric emptying.…”
Section: Introductionmentioning
confidence: 99%
“…GPR39 is known to signal through Gαs in addition to Gαq. 4 Thus, we tested compounds in a HEK293 cell line overexpressing the human GPR39 receptor and used forskolin as a reference compound to measure the maximal cAMP release. All compounds were active in Gαs signaling, with compound 3 as the most active both in terms of EC 50 value and maximal efficacy.…”
mentioning
confidence: 99%